2010
DOI: 10.1348/135910709x478664
|View full text |Cite
|
Sign up to set email alerts
|

Mediation by illness perceptions of the effect of personality and health threat communication on coping with the diagnosis of diabetes

Abstract: Objectives. (1) To examine the relationship of personality traits and diabetes health threat communication (DHTC) to the coping strategies of newly diagnosed diabetes patients; (2) to determine to what extent these postulated effects are mediated by illness representations (IRs). Design. A longitudinal prospective study based on the common sense model. Methods. Patients were assessed shortly after diagnosis and 2 years after the diagnosis of diabetes. Personality traits (Mini‐markers) were assessed at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 61 publications
2
33
1
Order By: Relevance
“…This previous study found that a more reassuring health message was associated with better coping, and that Illness Coherence and Personal Control fully mediated these relationships (Lawson et al, 2010). Our findings partially support this previous work, in that we found that Personal Control fully mediated the association between the doctor-patient relationship and diabetes-related distress.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This previous study found that a more reassuring health message was associated with better coping, and that Illness Coherence and Personal Control fully mediated these relationships (Lawson et al, 2010). Our findings partially support this previous work, in that we found that Personal Control fully mediated the association between the doctor-patient relationship and diabetes-related distress.…”
Section: Discussionsupporting
confidence: 90%
“…While type of diabetes was not associated with diabetesrelated distress, individuals with Type 1 diabetes had relatively higher scores on Timeline (Acute/Chronic), Consequences and Illness Coherence as well as lower scores on Treatment Control. These findings are in concordance with the notion that patients typically perceive Type 1 diabetes to be more severe than Type 2 (Lawson et al, 2010), but also suggest that Type 1 diabetes patients have a better perceived understanding of their condition.…”
Section: Further Younger Individuals Reported Relatively Reduced Persupporting
confidence: 87%
See 1 more Smart Citation
“…The research generally demonstrates that illness perceptions explain a significant proportion of the variance in physical and psychological outcomes in a range of illnesses (Dempster et al, 2011a;Dorrian, Dempster & Adair, 2009;Glattacker, Opitz & Jäckel, 2010;Kaptein et al, 2010). The relationship between illness perceptions and both psychological and physical outcomes has been well established among adults with Type 2 diabetes Lawson, Bundy, Belcher & Harvey, 2010;Searle, Norman, Thompson & Vedhara, 2007a;Searle, Norman, Thompson & Vedhara, 2007b;Searle et al, 2008;Skinner et al, 2006;Skinner et al, 2011;Sultan, Attali, Gilberg, Zenasni & Hartemann, 2011), and the findings of this research have been posited as a basis for interventions to improve well-being among this population.…”
mentioning
confidence: 78%
“…Illness perceptions encompass the patient's own understanding and beliefs about their illness, its effects, causes and progression. Illness perceptions have been found to predict recovery from a range of conditions, such as myocardial infarction 11,12 or surgery 13,14 and also seem to influence how patients cope with chronic conditions, such as diabetes 15,16 , chronic lung disease 17 or arthritis [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%